1993
DOI: 10.1093/cvr/27.11.2037
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced gene expression of calcium regulatory proteins in stunned porcine myocardium

Abstract: The results suggest specific repair mechanisms of stunned myocardium and point to the involvement of calcium regulatory proteins related to the sarcoplasmic reticulum in the pathogenesis of myocardial stunning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
1
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 0 publications
4
23
1
1
Order By: Relevance
“…Schaper's laboratory provided pioneering studies on alterations in gene expression in swine models of ischemia͞reperfusion (20,26). These studies examined specifically the time course of changes in genes encoding protooncogenes and calcium-handling proteins (20,26). In contrast, we applied recently developed techniques of gene screening to determine the global change in gene expression in response to transient ischemia, rather than selecting specific targets.…”
Section: Discussionmentioning
confidence: 99%
“…Schaper's laboratory provided pioneering studies on alterations in gene expression in swine models of ischemia͞reperfusion (20,26). These studies examined specifically the time course of changes in genes encoding protooncogenes and calcium-handling proteins (20,26). In contrast, we applied recently developed techniques of gene screening to determine the global change in gene expression in response to transient ischemia, rather than selecting specific targets.…”
Section: Discussionmentioning
confidence: 99%
“…3) as well as stunned myocardium (7,12). Because intracellular Ca 2ϩ overload is known to occur in I/R hearts (25, 26) and hypoxia-reoxygenated hearts (24), it is possible that intracellular Ca 2ϩ overload may produce alterations at the level of SR gene expression in I/R hearts.…”
Section: Discussionmentioning
confidence: 99%
“…More studies are needed to investigate the transcription factors regulating the expression of each gene under different diseased conditions. Studies conducted by Schaper and co-workers (7,12) showed an increase in the transcript levels for SERCA2a, PLB, and CQS due to one cycle of 10-min coronary occlusion and 90-min reperfusion (7), whereas two cycles of 10-min coronary occlusion followed by 60-min reperfusion under in vivo conditions showed a tendency toward a decrease in the mRNA levels. In fact, transcriptional modulation has been implicated as a major player in alterations of SR gene expression in cardiac pathology (12) as well as during cardiac differentiation and myogenesis (13,17).…”
Section: Discussionmentioning
confidence: 99%
“…In the porcine model of myocardial stunning (two periods of 10 rain coronary artery occlusion separated by 30 rain reperfusion) we and others have shown that reperfusion leads to the induction of several genes encoding proto-oncogenes [50,51], Ca 2+ binding proteins [52] and heat shock proteins (HSPs) [45,[53][54][55][56][57][58][59]. It has been observed that brief periods of myocardial ischemia and reperfusion do not only cause prolonged contractile dysfunction, but also increase the tolerance for irreversible damage during a subsequent sustained episode of ischemia ("ischemic preconditioning").…”
Section: Myocardial Stunningmentioning
confidence: 99%